ASSESSMENT OF WIND RESOURCE AND ENERGY POTENTIAL OVER AUCHI AND ENVIRONS, EDO NORTH, EDO STATE - Ogbomida, E.T.; Emeribe, C.N.; Abdullahi, M.; Chiemeke S.C.; Olatunji, J.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Wind energy is favored by areas with consistent and strong winds, stable financial investment, with strong policy for energy transition. As the country sets out programmes to sustainably transit from over dependence on fossil fuels to clean energy, there is need for preliminary assessment of energy resources of the country. Wind is an important source of renewable energy in Nigeria especially in the coastal, guinea savannah and sudano-sahel regions. Auchi town is a transition between savannah and tropical rainforest agro-climatic region of Nigeria, though more of savannah. This unique geographical feature coupled with ongoing energy transition initiatives of the Federal government aimed to tackle greenhouse gasses (GHGs) emission necessitated the need for the present study. The study aimed to evaluate the wind resources and energy potential of Auchi town and environs. Both field measurement, NUMET and NASA-SSE datasets were utilized. Regression analysis of field measurement with NIMET datasets yielded an R-Value (correlation factor) of 0.629 and an R2 value of 0.39 for Jattu – Atte Road, 0.623 and 0.388 for Barthony Petrol Station along Okene Road, and 0.623 and 0.388 for Auchi-Jattu respectively. The corresponding values with SSE data yielded R-Value of 0.722 and an R2 value of 0.521 for Jattu – Atte Road, 0.761 and 0.580 for Barthony Petrol Station along Okene Road, and 0.762 and 0.581 for Auchi-Jattu. These results indicated a better relationship between on-site and SSE historical data than those from NIMET. The annual average wind speed for Auchi data is 2.505 m/s using SSE data and 2.257 from NIMET data. The average wind speed recorded at Jattu – Atte Road, for the seven-day measurement period from is 2.268 m/s. In Barthony Petrol Station along Okene Road and Auchi-Jattu respectively sites the seven days averages were 2.268 m/s and 2.267 m/s respectively. Wind speed values were further subjected to Weibull distribution curve analysis to determine the power density. Result revealed that Power density, P (W/m2) area ranges from 164 W/m2 to 177.4 W/m2 at 10m and from 187.43 W/m2 to 247.35 W/m2 at 60m. This a good power density to support a hybrid wind energy project. However, there is need for more studies to determine the effects of other key parameters such as heights, turbulence on power yield as well as Land use and Land cover features that may affect wind projects in the study area.